2006
DOI: 10.1210/en.2006-0005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Protein 3 Has Opposing Actions on Malignant and Nonmalignant Breast Epithelial Cells that Are Each Reversible and Dependent upon Cholesterol-Stabilized Integrin Receptor Complexes

Abstract: IGF-binding protein (IGFBP)-3 is generally considered to have actions that counterbalance those of IGFs and is therefore being developed as a cancer treatment. In breast tumors, however, high levels are associated with aggressive tumors and poor prognosis. Consistent with this we have demonstrated that although IGFBP-3 and a non-IGF-binding fragment (serine phosphorylation domain peptide) reduced attachment and enhanced apoptosis of Hs578T breast cancer cells cultured on collagen or laminin, it promoted their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 49 publications
3
61
0
Order By: Relevance
“…These interactions are very analogous to those that we have found between IGFBP-3 and EGF. It has been reported that EGF regulates IGFBP-3 production (21, 22), and we have described in this study and previously that that the intrinsic effects of IGFBP-3 on cell growth also involves integrin receptor activation and phosphorylation of MAPK culminating in cell proliferation (5).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…These interactions are very analogous to those that we have found between IGFBP-3 and EGF. It has been reported that EGF regulates IGFBP-3 production (21, 22), and we have described in this study and previously that that the intrinsic effects of IGFBP-3 on cell growth also involves integrin receptor activation and phosphorylation of MAPK culminating in cell proliferation (5).…”
Section: Discussionsupporting
confidence: 71%
“…In addition there have been several reports that in breast tumors the expression of IGFBP-3 is positively associated with large, highly proliferative tumors and poor prognostic markers (14,15). Furthermore, we have previously reported that in contrast to its inhibitory effects on breast cancer cells, IGFBP-3 promoted the proliferation and survival of the relatively normal, non-malignant, anchoragedependent MCF-10A cells (12), which we also showed was dependent upon ␤1 integrins and subsequent activation of MAPK (5).…”
supporting
confidence: 60%
See 3 more Smart Citations